CODING THEORY APPLIED TO KU-ALGEBRAS - Samy Mohammed Mostafa; Bayumy Youssef; Hussein Ali Jad (Journal of New Theory)
The notion of a KU-valued function on a set is introduced and related properties are investigated. Codes generated by KU-valued functions are established and some interesting results are obtained